Medulloblastoma has a global impact on health related quality of life: Findings from an international cohort. (21st November 2019) - de Medeiros, Cynthia B.; Moxon‐Emre, Iska; Scantlebury, Nadia; Malkin, David; Ramaswamy, Vijay; Decker, Alexandra; Law, Nicole; Kumabe, Toshihiro; Leonard, Jeffrey; Rubin, Josh; Jung, Shin; Kim, Seung‐Ki; et al.
Abstract: Background: Understanding the global impact of medulloblastoma on health related quality of life (HRQL) is critical to characterizing the broad impact of this disease and realizing the benefits of modern treatments. We evaluated HRQL in an international cohort of pediatric medulloblastoma patients. Methods: Seventy‐six patients were selected from 10 sites across North America, Europe, and Asia, who participated in the Medulloblastoma Advanced Genomics International Consortium (MAGIC). The Health Utilities Index (HUI) was administered to patients and/or parents at each site. Responses were used to determine overall HRQL and attributes (ie specific subdomains). The impact of various demographic and medical variables on HRQL was considered—including molecular subgroup. Results: The majority of patients reported having moderate or severe overall burden of morbidity for both the HUI2 and HUI3 (HUI2 = 60%; HUI3 = 72.1%) when proxy‐assessed. Self‐care in the HUI2 was rated as higher (ie better outcome) for patients from Western versus Eastern sites, P  = .02. Patients with nonmetastatic status had higher values (ie better outcomes) for the HUI3 hearing, HUI3 pain, and HUI2 pain, all P  < .05. Patients treated with a gross total resection also had better outcomes for the HUI3 hearing ( P  = .04). However, those who underwent a gross total resection reported having worse outcomes on the HUI3 vision ( P  = .02). No differences in HRQL were evident as a function of subgroup. Conclusions: By examining an international sample of survivors, we characterized the worldwide impact of medulloblastoma. This is a critical first step in developing global standards for evaluating long‐term outcomes. Abstract : Despite the significant advances in our knowledge of medulloblastoma and the resulting advantages of improved therapy, health related quality of life (HRQL) requires further attention globally. Assessing HRQL in an international sample, we found that the majority of patients reported having moderate or severe overall burden of morbidity. This demonstrates the need for the development of universal standards for assessing HRQL through international collaboration in order to improve the lives of all pediatric medulloblastoma survivors.